Health care personnel's attitudes on family presence during resuscitation - Ahayalimudin, Nurul'Ain; Zulkifly, Nurul Farzela (2016)
Traditionally, resuscitation is done by groups of health care personnel alone where family members are excluded from witnessing this procedure.However, family presence during resuscitation (FPDR) remained a controversial issue worldwide although some recognized professional bodies now offering support to this practice. Objectives: This study attempts to examine the attitudes of healthcare personnel towards allowing FDPR in Malaysia, to determine the association between socio-demographic data and to compare attitudes towards family presence during resuscitation in a different profession. Methodology: A cross-sectional study with simple random sampling was carried out to 180 health care personnel (n=70doctors, n=81 Registered Nurses; n=79 Assistant Medical Officers) working at the Emergency & Trauma Department, Coronary Care Unit and Intensive Care Unit of Sungai Buloh Hospital, Selangor. A total of 153 health care personnel responded with a response rate of 88%. The chi-square test was used to identify the association of socio-demographic data with the attitude towards FPDR among health care personnel. Results: It was shown that 74.1% of health care personnel in this study have negative attitudes towards FPDR. There was a significant association between age (p=0.038) and previous experience (p=0.004) with an attitude towards FPDR. The findings showed there is no difference between professions of health care personnel attitude (p=0.410). Conclusion: The findings clarified that majority of health care personnel in this study have a negative attitude towards FPDR.